Experimental Analysis of the Effect of Valve Clearance Variations on the Performance and Emissions of Suzuki G15A Gasoline Engines in the Philippines - Mark Anthony Eduardo; Emilio Carlojay; Tonieli Jomaric; Angelo Ramirez (Lembaga Penelitian dan Ilmu Pengetahuan JEPIP, 2025)
This study analyzes the effect of intake valve-clearance variation on the performance and exhaust-emission characteristics of the Suzuki G15A four-stroke gasoline engine, widely used in light commercial vehicles in the Philippines such as the Suzuki APV and Super Carry. The research was motivated by the country’s rising fuel consumption—about 31 million barrels per year—and the high contribution of gasoline vehicles, which account for around 70 % of CO emissions in Metro Manila. Experimental tests were performed using four valve-clearance settings (0.10, 0.15, 0.20, and 0.25 mm) under controlled tropical conditions (30 ± 2 °C, 80 % humidity) with Petron RON 91 fuel. The results show that increasing the valve clearance to 0.25 mm raised cylinder pressure from 13.9 to 14.9 kg/cm² and improved indicated power from 16.9 kW to 63.6 kW at engine speeds between 1000 and 3500 rpm. The Brake Specific Fuel Consumption (BSFC) decreased from 100.88 to 44 g/kWh, indicating higher combustion efficiency. Emission analysis revealed that a 0.15–0.20 mm clearance produced the best balance between power and low emissions: CO and HC levels decreased while CO₂ increased up to the optimum point at 2500–3000 rpm, reflecting more complete combustion. The study’s findings suggest that the 0.15–0.20 mm clearance range offers the optimal compromise between fuel economy, power output, and emission reduction. This research provides novel experimental evidence on the G15A engine under Philippine tropical conditions, and its outcomes can support the development of a national adaptive valve-clearance standard to promote energy efficiency and environmental sustainability in the country’s transportation sector.